Unlocking Value From By-Products in Slovenia’s Bioeconomy - Potrč, Sanja; Bogataj, Miloš; Kravanja, Zdravko; Novak Pintarič, Zorka; Marina Bajić (7th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings, 2025)
Slovenia has significant raw material potential for the development of the bioeconomy. The Interreg Central Europe project TeBiCE focuses on Territorial Biorefineries for a Circular Economy and explores the utilization of biomass, by-products, and residues from primary production and the agri-food processing industry as new sources for producing high-value products. In Slovenia's contribution to the TeBiCE project, three key sectors were evaluated: fruit production and processing, oil production and processing, and the wood processing industry (timber). The potential for developing value chains in Slovenia was assessed using the Value Chain Generator® artificial intelligence tool (VCG.AI). Three value chains were outlined, where polyphenols, biochar, and pectin can be produced through the application of supercritical fluid extraction (SFE), pyrolysis, and enzymatic extraction. Biochar and polyphenols show high potential for exploiting by-product biomass in Slovenia. The VCG.AI tool was demonstrated to be an applicable resource for the fast and effective evaluation of by-products' potential for developing value chains.